Analyze thermal behaviour and design performance of a passive vernalization-vertical farming system for tropical garlic production - Ahmad Arifuddin; Azzahra Al Fatikhana; Hasna-ur Rusyda Afifatul ‘Ulya (Journal of Agrosociology and Sustainability, 2026)
Background: Indonesia exhibits a critical dependency on garlic imports, satisfying 96.8% of national demand (575,000 tons) and positioning the nation as the world's largest importer in the first half of 2024. This reliance undermines local competitiveness, necessitating urgent improvements in domestic productivity. However, cultivation is hindered by two primary constraints: limited arable land and the crop's high sensitivity to heat during vernalization. Vernalization, a cold-induced process (5°C–13°C) essential for transitioning vegetative buds to reproductive stages, presents a significant challenge in tropical climates. Methods: This study proposes a novel device integrating a pipe-based vertical cultivation system with a passive vernalization chamber. Utilizing evaporative cooling and locally sourced materials like clay and coconut fiber, it provides low-cost, energy-efficient operation. The device’s performance and feasibility in tropical regions were evaluated through literature review of heat transfer and material properties. Findings: The Tropiverna system, integrating vertical cultivation with passive and active cooling mechanisms, effectively maintains stable low temperatures for garlic vernalization in tropical conditions. The combination of evaporative cooling via clay-coconut fiber pots and Peltier thermoelectric modules reduces heat stress, enhances temperature uniformity, and improves energy efficiency. This design optimizes land use and is projected to increase garlic productivity by up to 307.79% per hectare. Conclusion: Integrates verticulture with a hybrid cooling system utilizing zeer pot principles and Peltier modules, theoretically resolves Indonesia’s land and climatic constraints by optimizing vernalization conditions, thereby serving as a sustainable, scalable strategy to reduce import dependency and strengthen national food sovereignty. Novelty/Originality of this article: The novelty of this research lies in the specific application of a cost-effective vernalization system within a vertical farming architecture designed for the tropics, offering an adaptive solution for sustainable national food sovereignty.